Perancangan Interior Creative Collaborative Space di Surabaya - Patrick Devo Megaliong (Intra, 2016)
People in Surabaya need facility that can be use to accommodate creative activity in work or exchange ideas. One of the facility to accommodate is Co-Working Space. The Co-Working Space that is needed is hoped to accommodate working activities in one area and gain enthusiasm of the creative workers to create and exchange ideas With design method adapted from Campbell, emphatize is where collection of data is collected by various means such as field data research, typology research, as well as literature data. Then proceed with define, which focus on preparation of the data that has been requested. Then, on the third step of process there is ideate. This step is where we are focusing the design ideas. After it, we focused on creating mockups from the design. And the last step is the test carried out with the aim of getting some feedback. Creative Collaborative space designed wiith open space area so that work activity can be fulfilled in one big area without any wall that matter. Creative Collaborative Space has many facility to enthusiast many uses such as meeting room and talk room can be used for brainstorming, talk room used for seminar, pecha-kucha, and similar activity, while meeting room can be used for meeting with client or else.